A Cross Sectional Study on Patients (International Journal of Biomedical Research, 2019)
Background and Objectives: No studies from India have reported perceptions of patients regarding use of alternative therapies along with allopathy for Alcohol Use Disorder (AUD). The present study was conducted to assess perceptions of patients regarding treatments of AUD. Methodology: Patients treated for AUD for 3 or more months were enrolled in a cross-sectional study after Institutional Ethics Committee permission and written informed consent from a deaddiction centre of a tertiary care hospital. They were interviewed using a pre-validated questionnaire for pattern of use and perceptions about allopathy and alternative medicines. Data was analysed using descriptive statistics. Results: Of 100 male patients between 31-50 yrs of age, 97% were dependent on alcohol for over 2 years. A total of 86% received only allopathy treatment whereas 14% took combination of alternative and allopathy therapies. All were offered counselling at deaddiction center. Out of 14 patients who took combination of allopathy and alternative therapy, 10 found allopathy to be more effective overall while 4 found both allopathy and alternative therapy equally effective. Regarding the perception and experience about the deaddiction treatment, 34/86 reported abstinence was possible due to treatment, 31/86 reported decrease in withdrawal symptoms, 15/86 stated decreased craving with allopathy treatment. Almost half the number of patients taking combination therapy (6/14) reported decrease in craving and 4/14 reported abstinence. Lorazepam was used in all cases as a part of initial detoxification treatment. Conclusion: Allopathy drugs were perceived to be more effective even in patients who were on combination of allopathy and alternative therapy. Use of alternative therapies was not prevalent and favoured as compared to allopathy.